Estimation of aquifer recharge measured by the isotopic fractionation of water vapor and the hydrological balance of the soil in the dry tropical forest of Costa Rica - Barrientos Peña, Andrea Noemí (Centro Agronómico Tropical de Investigación y Enseñanza (CATIE), 2014)
Tesis (Mag. Sc.) -- CATIE, 2022